Pengaruh Good Corporate Governance Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan - Siti Ma'rifatus Syifa; Rr. Tjahjaning Poerwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study was conducted to find empirical evidence that strengthens the research model and analyzes and becomes learning material regarding the effect of Good Corporate Governance and Company Size on Company Financial Performance. The population used in this study are Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2022 period. The sample was determined using the Purposive Sampling (Judgmental Sampling) method, namely sample research with criteria. Based on the sample selection obtained from 26 companies, 104 samples were processed (4 years). The data analysis technique used multiple linear regression analysis with the SPSS version 25.0 program. The results of the study found empirical evidence that Institutional Ownership and Company Size have a significant effect on the company's financial performance. While Managerial Ownership, Board of Directors, Board of Independent Commissioners and Audit Committee have no significant effect on the company's financial performance. Keywords: Institutional Ownership; Managerial Ownership; Board of Directors; Independent Board of Commissioners; Audit Committee; Company Size; Company Financial Performance.